Essentiality of seed standards for cultivation of medicinal plants — a review (Current Horticulture, 2024)
Seeds play a critical role in agriculture, serving as the primary unit of plant propagation. Seed quality parameters of a notified variety of crops have been published through gazette notification from time to time and compiled. Indian Minimum Seed Certification Standards are available for about 150 crops grown in India. However, no such seed standards have been formulated for medicinal and aromatic plants grown by farmers in India. Therefore, quality of seed made available to farmers cannot be regulated as envisaged under Seeds Act. Several attempts have been made to formulate seed standards and seed testing protocols for important medicinal crops cultivated by farmers. Those studies/attempts were made on different seed parameters of the seeds of the species at different centres, viz. IARI, New Delhi; DMAPR, Anand, Gujrat and IIHR, Bengaluru. For seed lot size and sample size, seeds indicated weights of lots which was derived from a nominal thousand seed weight for each species expected to be adequate for the majority of samples tested. Working sample for purity analysis considered was the weight of 2,500 seeds and working sample for count of other species was the weight of 25,000 seeds. For example, maximum weight of lot for Plantago ovata would be 10,000 kg for which submitted sample would be 50 g and it would be 5 g for working sample for purity analysis and 50 g for working sample for count of other species. In this study further pure seed (PSD) was defined based on ISTA (2003) and ISTA (2012), for example, in Lepidium sativum, PSD number is given as PSD 11 which states that in the seed a portion of testa is attached in which seeds and pieces of seed entirely without testa are regarded as inert matter. In P. ovata, pure seed (minimum) is 98% in both foundation and certified seed, of which 2% is inert matter. In this case total weed seed could be 10/kg, other crop seed 10/kg and germination should be 85% (minimum) with maximum moisture 10%. Likewise, seed standards and seed testing protocols of all the medicinal species taken from time to time have been standardized which would prove useful for seed quality assurance in medicinal plant sector. Further, it would be used towards notification of a variety under Seeds Act and also for the conservation of germplasm in gene/seed bank.
Keywords: Germination; Medicinal plants; Plantago ovata; Seeds; Seed standard